2008
DOI: 10.1007/s12031-008-9129-8
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Analyzing Mitochondrial Movement: Inhibition by Paclitaxel in a Pheochromocytoma Cell Model

Abstract: A method was developed to assess mitochondrial movement in the living cell that is dependent, in part, on microtubule and/or associating protein interactions. The leader sequence from cytochrome-c was used to drive DsRed2 fluorescent proteins to accumulate in the mitochondria, thus enabling to follow mitochondrial (cytochrome-c's) movement. For calculating the percentage of mitochondrial movement, an image-processing program was used (ImageJ). Paclitaxel, an antitumor agent, is a potent microtubule-stabilizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
3
8
0
Order By: Relevance
“…We found that in both NT and PC1/3 KD cells, the Paclitaxelinduced up-regulation of Tuba1ac and Tuba4a was accompanied by the co-upregulation of a highly significant number of mitochondria-related molecules (Figure 3Ci). This result was in line with previous studies that demonstrated that Paclitaxel targets mitochondria 33 , possibly as a direct consequence of microtubule network alterations 34 . Interestingly, we also observed that Tuba1ac/Tuba4a co-expression networks comprised immune-related molecules that, for some, were distinct when comparing Paclitaxel-treated NT cells vs. Paclitaxel-treated PC1/3 KD cells.…”
Section: Paclitaxel Induces Secretion Of Pro-inflammatory Cytokines Bsupporting
confidence: 93%
“…We found that in both NT and PC1/3 KD cells, the Paclitaxelinduced up-regulation of Tuba1ac and Tuba4a was accompanied by the co-upregulation of a highly significant number of mitochondria-related molecules (Figure 3Ci). This result was in line with previous studies that demonstrated that Paclitaxel targets mitochondria 33 , possibly as a direct consequence of microtubule network alterations 34 . Interestingly, we also observed that Tuba1ac/Tuba4a co-expression networks comprised immune-related molecules that, for some, were distinct when comparing Paclitaxel-treated NT cells vs. Paclitaxel-treated PC1/3 KD cells.…”
Section: Paclitaxel Induces Secretion Of Pro-inflammatory Cytokines Bsupporting
confidence: 93%
“…A recent study showed that paclitaxel, a microtubule-stabilizing drug, could impair the function and motility of mitochondria through enhancing the stability of tubulin polymers. 35 These findings support our contention that mitochondrial defect may induce acetylation and detyrosination of ␣-tubulin to increase mirotubule rigidity, which in turn contributes to the alteration of mitochondrial network in the skin fibroblasts of CPEO patients. In a further study, we showed that a decrease in the expression of tubulin deacetylase Sirt2 was associated with the accumulation of acetylated ␣-tubulins in the skin fibroblasts of CPEO patients (Fig.…”
Section: Lysine Acetylation In Cpeo Syndromesupporting
confidence: 88%
“…Varied hypotheses have been proposed, including: compromised transport of proteins and organelles (Shprung and Gozes, 2009, Shemesh and Spira, 2010, LaPointe et al, 2013), changes in receptor and channel localization and function (Flatters and Bennett, 2004, Matsumoto et al, 2006, Xiao et al, 2007, Nieto et al, 2008, Chen et al, 2011, Okubo et al, 2011, Kawakami et al, 2012, Hara et al, 2013, Chen et al, 2014) and/or activation of an immune response (Siau et al, 2006, Peters et al, 2007, Pevida et al, 2013, Warwick and Hanani, 2013, Zhang et al, 2013, Li et al, 2014, Li et al, 2015). Stabilization of microtubules can alter both anterograde and retrograde axonal transport of mitochondria along the microtubules (Nennesmo and Reinholt, 1988, Morris and Hollenbeck, 1995, Nakata and Yorifuji, 1999, Theiss and Meller, 2000, Shemesh and Spira, 2010, Bober et al, 2015).…”
Section: Discussionmentioning
confidence: 99%